Attitudes of secondary school students with diabetes towards physical education and sports classes (a field study in secondary schools in the state of Djelfa) - guiall, mourad (sports creativity, 2025)
The current study aims to identify the attitudes of secondary school students with diabetes towards physical education and sports classes, and to identify differences in these attitudes according to the variables of gender and age. On the other hand, this study aims to raise awareness among this group about the benefits of practicing sports, both in secondary school and outside of it.